COVID-19 perceptions, subjective norms, and perceived benefits to attitude and behavior of continuous using of medical mask - Yasa, Ni Nyoman Kerti; Rahmayanti, Putu Laksmita Dewi; Telagawathi, Ni Luh Wayan Sayang; Witarsana, I Gusti Agung Gede; Liestiandre, Hanugerah Kristiono (Linguistics and Culture Review, 2021)
The purpose of this study was to examine and explain the effect of COVID-19 Perception, subjective norms, and Perceived Benefits on attitudes and Behavior continuous use of medical mask. The population of this study is people in Indonesia who have used medical masks for at least a year. The size of the sample used is 146 people with purposive sampling method. The analytical technique used is Path Analysis using SEM-PLS. The results showed that the COVID-19 perception, subjective norm, and perceived benefits had a positive and significant effect on attitudes and behavior in using medical masks continuously, and attitudes about using medical masks also had a positive and significant effect on the intention to continue using them continuously. Therefore, it is important for regional leaders to continue to disseminate and educate about the importance of continuous use of medical masks in order to prevent the spread of disease due to COVID-19 and maintain public health by providing information about COVID-19 disease and the benefits of using this medical mask.